Accompanying artery of sciatic nerve as recipient vessel for free‐flap transfer: A computed tomographic angiography study and case reports. Issue 4 (8th September 2014) - Miyamoto, Shimpei; Fukunaga, Yutaka; Fujiki, Masahide; Nakatni, Fumihiko; Tanzawa, Yoshikazu; Sakuraba, Minoru
<x xml:space="preserve">Abstract</x> Suitable recipient vessels for free‐flap transfer are hard to find in the posterior thigh. To investigate the versatility of accompanying artery of sciatic nerve as a recipient vessel in this region, we performed computed tomographic angiographic study of 20 consecutive healthy thighs in 10 patients. The presence and internal diameter of the accompanying artery were studied. The accompanying artery of the sciatic nerve was present in 11 thighs (55%) and the internal diameter of the artery at the mid‐thigh level ranged from 2.1 to 3.2 mm. We used this artery as a recipient vessel for free flaps transferred to reconstruct extensive thigh defects in three patients with sarcomas. In all patients the flaps survived without vascular compromise. No sensory or motor dysfunction in the sciatic nerve distribution occurred in any patients. We believe that the accompanying artery of the sciatic nerve may be a recipient vessel for free‐flap transfer in selected patients. © 2014 Wiley Periodicals, Inc. Microsurgery 35:284–289, 2015.